Metabolic profile of alkaloids in Rhizoma Coptidis in rat plasma, urine and feces after oral administration using ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry. (13th March 2020) - Liu, Yi; Zhang, Ye; Meng, Qi; Long, Jianglan; Wang, Man; Zhang, Xu; Yan, Can; Yan, Dan
Abstract : Rationale: Rhizoma Coptidis (RC) has been used to treat diabetes, pertussis, bacillary dysentery, sore throat, eczema, and aphtha for thousands of years. Alkaloids are the major components in RC, and its curative effect is achieved by oral administration. However, information on its composition in vivo is weak. Methods: In this study, ultra‐high‐performance liquid chromatography coupled with quadrupole time‐of‐flight mass spectrometry (UPLC/QTOF‐MS) was used to analyze the major active components and their metabolites in rat plasma, urine and feces after oral administration of RC extract. Results: A total of 96 compounds including 8 prototype compounds and 88 metabolites were identified, and hydroxylation, reduction, demethylenation, demethylation, dehydrogenation, sulfation, glucuronidation and methylation were the major metabolic pathways. Conclusions: This study analyzed metabolic processes of the major active components in RC in vivo, which provided important information for its active composition and in vivo mechanism research. Meanwhile, metabolic profile studies on representative compounds provided valuable reference materials to elucidate the full‐scale metabolites of RC.